PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KOPERASI CERMAT PALEMBANG - Muhammad Ridwan; Noviarni .; Dede Saputra (JURNAL KOMPETITIF, 2018)
In this study, the authors examine how the Influence of Leadership and Motivation on Employee Performance at Cermat Palembang Cooperative. In this study because the total population of only 34 people, then all employees as many as 34 people sampled by technique Proportionate Stratified Random Sampling. From the results of research, There is a positive and significant influence of Leadership and Motivation together on Performance, From Table F Test above can be seen that the value of F 10.796 and the value of sig is 0.000. From the significance level value means sig <0.05 which means there is influence Motivation and Leadership together to Performance. There are positive and significant influence of Leadership on Performance, From Multiple Linear Regression Analysis table can be seen that for Leadership variable, t value = 3.658 and value sig = 0.001. From the significance level value means sig <0,05 which means there is influence of Leadership to Performance. There is a positive and significant influence Motivation on Performance, From the table of Multiple Linear Regression Analysis can be seen that for the motivation variable t value = 2.107 and the value of sig = 0.044. From the significance level value means sig <0,05 which means there is influence Motivation to Performance. Keywords: Employee Performance, Leadership, Motivation